Study the forest, not only the trees: Environmental exposures, not genomes, generate most health disparities - Thompson, Taylor V.; Crocker, Katherine C. (Frontiers in Genetics, 2022)
As sequencing and analysis techniques provide increasingly detailed data at a plummeting cost, it is increasingly popular to seek the answers to medical and public health challenges in the DNA sequences of affected populations. This is methodologically attractive in its simplicity, but a genomics-only approach ignores environmentally mediated health disparities, which are well-documented at multiple national and global scales. While genetic differences exist among populations, it is unlikely that these differences overcome social and environmental factors in driving the gap in health outcomes between privileged and oppressed communities. We advocate for following the lead of communities in addressing their self-identified interests, rather than treating widespread suffering as a convenient natural experiment.